2012
DOI: 10.7314/apjcp.2012.13.8.4177
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Methylation Status of DNA Repair Gene (hMLH1) in Gastric Carcinoma Patients of the Kashmir Valley

Abstract: Cancer is a multi-factorial disease and variation in genetic susceptibility, due to inherited differences in the capacity to repair mismatches in the genome, is an important factor in the development of gastric cancer (GC), for example. Epigenetic changes, including aberrant methylation of 5/CpG islands in the promoter regions of mismatch repair (MMR) genes like hMLH1, have been implicated in the development of various types of GC. In the present study we evaluated the role of hMLH1 promoter hypermethylation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…P16 inhibits cell cycle progression, and has been found to correlate with poor tumor differentiation, lymph node metastasis and poor survival. The frequency and specificity of P16 were found to be 30.4–44.2 and 76–100%, respectively (15,18,20). RUNX3 belongs to the RUNX family of transcriptional factors, and has been found to correlate with depth of tumor invasion, lymph node and distant metastasis.…”
Section: Discussionmentioning
confidence: 95%
“…P16 inhibits cell cycle progression, and has been found to correlate with poor tumor differentiation, lymph node metastasis and poor survival. The frequency and specificity of P16 were found to be 30.4–44.2 and 76–100%, respectively (15,18,20). RUNX3 belongs to the RUNX family of transcriptional factors, and has been found to correlate with depth of tumor invasion, lymph node and distant metastasis.…”
Section: Discussionmentioning
confidence: 95%
“…15 In a study conducted with gastric carcinoma patients, researchers showed that mutL homolog 1 (MLH1) methylation was found to be more common in males (82.1%) compared to females (35.75%). 39 In the current study, male patients (81.25%) are composed of the majority of individuals in hypermethylation observed group. In addition, methylation of WT1, ESR1, CDH13, MSH6, CD44 and PAX5 genes were detected at a higher frequency in men compared to women.…”
Section: Discussionmentioning
confidence: 99%
“…These DNA repair genes (with DNA repair pathways indicated) were NEIL1 (BER), NEIL3 (BER), DCLRE1C (NHEJ), NHEJ1 (NHEJ), GTF2H5 (NER), and CCNH (NER). Lynam-Lennon et al [71] found that miR-31 is over- Colorectal [17] MGMT 46% 34% Colorectal [19] MGMT 47% 11% Colorectal [60] MGMT with MSI 70% 60% Colorectal [19] MSH2 13% 5% Colorectal [61] MBD4 Frequent Frequent Colorectal [62] ERCC1 100% 40% Colorectal [62] PMS2 88% 50% Colorectal [62] XPF 55% 40% Colorectal [63] WRN 29% 13% Stomach [64] MGMT 88% 78% Stomach [65] MLH1 73% 20% Esophagus [66] MLH1 77%-100% 23%-79% expressed in 47% of esophageal cancers and examined the consequences of over-expression of miR-31 in these cancers. Using a cell line, they first tested the effect of over-expression of miR-31 on the expression of 84 DNA repair genes.…”
Section: Dna Repair Genes In Gi Cancersmentioning
confidence: 97%